Effect of Individual Attributes toward Financial Management Behavior through Locus of Control - Andi Amri; Tri Widyastuti; Syamsul Bahri; Zulmi Ramdani (Faculty of Economic and Business, 2023)
Only a few studies have examined the use of comprehensive variables in determining financial management behavior, though the model involves many other variables. Therefore, this study aimed to examine the locus of control as a mediator variable in the effect of financial attitude and knowledge, income, and spiritual intelligence on financial management behavior. It used a quantitative descriptive method and involved 391 respondents determined through convenience sampling. The results showed that financial attitude and spiritual intelligence significantly impact financial management behavior through locus of control. Whereas in the other two variables, namely financial knowledge, and income, the role of the mediator does not function effectively, so it does not have an indirect effect. These findings have implications for individuals to practice financial readiness in daily financial life. The information obtained also strengthens the role of self-control in financial management.JEL Classification: G40, G41How to Cite:Amri, A., Widyastuti, T., Bahri, S., & Ramdani, Z. (2023). Effect of Inidvidual Attributes toward Financial Management Behavior through Locus of Control. Etikonomi, 22(2), 443 – 456. https://doi.org/10.15408/etk.v22i2.26563.